Shaping Indonesia’s Digital Future: Relationship Between Public Education Expenditures and ICT Competence - Dwipatna, I Made Jyotisa Adi; Darwin, Dirmansyah; Ngoyo, Muh Fardan (PT FORMOSA CENDEKIA GLOBAL, 2026)
The acceleration of digital transformation has significantly enhanced information and communication technology (ICT) competence among Indonesian citizens, thereby strengthening the nation’s overall competitiveness. Despite this progress, there remains a need to understand the extent to which government education spending influences the improvement of ICT skills in both the short and long term. This study investigates the dynamic effects of education expenditure on ICT competence in Indonesia using provincial-level panel data sourced from the Indonesian Central Bureau of Statistics and the Ministry of Finance, covering the period from 2015 to 2023. The analysis employs the Generalized Method of Moments (GMM) to capture both temporal and cross-sectional variations. The results reveal that, in the short term, government education spending has a negative effect on ICT competence, possibly due to implementation delays or inefficiencies in resource allocation. However, in the long term, education spending contributes positively and significantly to the enhancement of ICT competence, indicating the cumulative benefits of sustained investment in education. Furthermore, internet access is consistently found to have a positive impact on ICT competence, emphasizing the importance of digital infrastructure. These results imply that consistent and well-targeted education investments, particularly in digital literacy and infrastructure, are essential for sustaining long-term ICT competence and supporting Indonesia’s digital transformation agenda